A aprendizagem da docência de professoras que atuam no 1º e 2º ciclos do ensino fundamental - Damasceno, Kelly Katia (2006)
This research aims at investigating how the teachers who teach in first and second cycles of basic education construct and reconstruct the teaching learning process. This study is classified like an investigation of qualitative type, carried out with six teachers of a primary school in Varzea Grande, state of Mato Grosso, in Brazil. The main instruments used for the data gathering were written and verbal narratives. The theoretical bases are anchored in literature about teaching learning and teachers’ formation and teachers’ knowledge and also the use of narratives as a mean of reflexive and investigative strategies. were also used. Based on the given literature we also counted on with some international and national theoreticians as Knowles & Cole (1994), Marcelo (1999), Imbernón (2004), Nóvoa (1992), Shulman (2004), Mizukami et. al. (2002), Hunter (2003), Arroyo (2003), Freitas (2004), among others. The analysis of the data reveiled the configuration of two thematic axles: the first axle, named "the different formative contexts", we consider aspects, such as: the experiences (personal, professional, institucional and organizacional), the initial formation (teaching and pedagogic) and the continuous formation deeply experienced by the studied teachers.The second axle, named "the context of the studied teachers ‘performance: the cycle",we consider the following aspects: the formation of the studied teachers for acting in a context organized for cycles, the conditions of teaching process the researched subjects, the necessary organization of the work in classroom and knowledge of the teaching performance. In this way, the findings revealed that the there is a continuous process that has been existing mixed by personal and professional passage of deeply experiences lived in different contexts. The findings also reveiled that the teaching learning process has been constructed of different ways, based on the differences in personal and professional histories, on the formation passages and experience, on their performances in the context of the cycles, thus, the learning process has been unchained based on the contribution of the teachers pairs, their specific context, their requirements and necessity of new teaching knowledge.